2020
DOI: 10.11604/pamj.2020.37.282.26583
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of the breast: analysis of 17 cases

Abstract: Tuberculosis constitutes a major public health problem in the world. Certain extra-pulmonary locations of tuberculosis disease are very exceptional. Amongst these, tuberculosis of the breast is rare even in countries where this infection is endemic. This form of tuberculosis is characterized by clinical and radiological polymorphisms and might mimic other diseases, especially breast cancer. This retrospective study is entailing seventeen patients treated in the Onco-Gynecology Department of the Mohammed VI Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Studies support the idea that, in most cases, the constitutional symptoms of tuberculosis (fever, weight loss, night sweats, or general deterioration) are rarely seen in BTB (Bouziyane et al, 2020;Fatima & Naz, 2019;Khodabakhshi & Mehravar, 2014). There is a clear predilection of breast tuberculosis lesions for the outer quadrants, probably due to the proximity to the axillary region from which retrograde lymphatic spread (Gupta et al, 2017).…”
Section: Clinical Conditionmentioning
confidence: 86%
See 3 more Smart Citations
“…Studies support the idea that, in most cases, the constitutional symptoms of tuberculosis (fever, weight loss, night sweats, or general deterioration) are rarely seen in BTB (Bouziyane et al, 2020;Fatima & Naz, 2019;Khodabakhshi & Mehravar, 2014). There is a clear predilection of breast tuberculosis lesions for the outer quadrants, probably due to the proximity to the axillary region from which retrograde lymphatic spread (Gupta et al, 2017).…”
Section: Clinical Conditionmentioning
confidence: 86%
“…Breast tissue is highly resistant to mycobacteria. Since it provides a sterile atmosphere for the survival and proliferation of bacilli, such as spleen and skeletal muscle, through the two immune modalities, innate by the macrophage that phagocytoses the bacilli and cell-mediated T4 lymphocytes through the cytokines they produce (Bouziyane et al, 2020;Haitz et al, 2019). This resistance explains the difficulty of diagnosis and the rarity that Breast Tuberculosis (BTB) presents, commonly affecting young, multiparous and lactating women (Hammami et al, 2021;Fatima & Naz, 2019).…”
Section: Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest incidence of TBm occurs in developing countries, such as India, where the reported incidence of TBm varies between 0.64% and 3.59% of patients with TB [3, 11]. Conversely, the incidence of TBm in first-world countries is lower and only represents 0.1% of breast lesions examined histologically [12]. A literature review found no studies have documented the histopathological findings in the context of HIV co-infection in Sub-Saharan Africa, hence the rationale for this study.…”
Section: Introductionmentioning
confidence: 99%